2006
DOI: 10.1007/s00701-006-0740-6
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the factors influencing bone graft infection after delayed cranioplasty

Abstract: Autoclaved and autogenous bone grafts and PMMA have a significantly higher rate of graft infection. Titanium mesh has the significantly lowest rate of graft infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
204
2
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(227 citation statements)
references
References 36 publications
11
204
2
10
Order By: Relevance
“…We found no significant association of age, sex, DM, and mechanism of injury (SAH, trauma, ischemic stroke) with postcranioplasty infection, which is consistent with the published literature. 22,29 Reoperation for hematoma showed no significant effect in our study, even though the need for multiple procedures has been shown to increase the risk of cranioplasty site infection. 29,43,47 On the other hand, Cheng et al's work 9 showed that the number of procedures does not affect the risk of graft infection following cranioplasty.…”
Section: Timing Infection and Hydrocephaluscontrasting
confidence: 56%
“…We found no significant association of age, sex, DM, and mechanism of injury (SAH, trauma, ischemic stroke) with postcranioplasty infection, which is consistent with the published literature. 22,29 Reoperation for hematoma showed no significant effect in our study, even though the need for multiple procedures has been shown to increase the risk of cranioplasty site infection. 29,43,47 On the other hand, Cheng et al's work 9 showed that the number of procedures does not affect the risk of graft infection following cranioplasty.…”
Section: Timing Infection and Hydrocephaluscontrasting
confidence: 56%
“…17 However, other data suggest that an increased interval increases both the incidence of complications and the risk of flap contamination. 5,11,13 A systematic review of adult cranioplasty showed no effect of timing on the rate of complications. 20 Likewise, our analysis revealed only 1 study in which the timing of cranioplasty was found to be associated with the risk of complications, along with several that showed no such association.…”
Section: Timing Of Cranioplastymentioning
confidence: 99%
“…Bone flap/graft resorption and infection [8,9], donor site morbidity, inadequate quantity of graft harvestable to bridge large cranial defects, prolonged intra-operative time, intraoperative blood loss and requirement of transfusions, need for surgical expertise and delayed post operative recovery [10] are definite drawbacks of autografting. Advanced age, presence of comorbidities, poor general condition of the patient, difficulties with bone flap storage, acute case scenarios and anatomical constraints can lead to difficulty in autografting or to the loss of the excised bone flap in a large number of cases [11,12]. At times, complications may result following Autogenous bone grafting, such as surgical site infection (SSI), graft/bone flap exposure, resorption, migration, hematomas and seromas [13].…”
Section: Introductionmentioning
confidence: 99%